If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 51 = 16d + 3 Reorder the terms: 51 = 3 + 16d Solving 51 = 3 + 16d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-16d' to each side of the equation. 51 + -16d = 3 + 16d + -16d Combine like terms: 16d + -16d = 0 51 + -16d = 3 + 0 51 + -16d = 3 Add '-51' to each side of the equation. 51 + -51 + -16d = 3 + -51 Combine like terms: 51 + -51 = 0 0 + -16d = 3 + -51 -16d = 3 + -51 Combine like terms: 3 + -51 = -48 -16d = -48 Divide each side by '-16'. d = 3 Simplifying d = 3
| -2(u+8)=-5u-46 | | y+8y=6 | | 3/1/9-c=3/1/4 | | 3r=9/10 | | 26+11b=70 | | 7(-8-37)= | | 2x=5*7 | | -6+x/4=-4 | | 275=15(x-55)+50 | | 59=12m+35 | | 14-5(-4x)=1 | | 3r=7/8 | | 7c+19=68 | | 4k-4= | | 2g/3-3g=1/2 | | .50(x)-3=6 | | (-7)(-12x)(-3)=1 | | 3x+17=7(x-1) | | 4k-k= | | y^2+(y-2)(y-2)=(y-4)(y-4) | | 6-2x=3x+6 | | 5*4=7*x-2 | | N=7/8 | | 4x^2-4x-16=0 | | .5[85x-25(x-2)]=1 | | 25z^2=-10z | | 6-2x=3x | | 6y+13=35 | | 7(x+7)+2=11x-4(x-5) | | 2(x-5)=5(x-7) | | y=1/5*8-2 | | 80=8+9c |